COMPUTATIONAL STUDIES ON THE COGNATE AND NON-COGNATE AMINOACYL-tRNAs - Monajemi, Hadieh; Mohd. Zain, Sharifuddin; Wan Abdullah, Wan Ahmad Tajuddin (Malaysian Journal of Science, 2011)
Although kinetic proofreading plays a major role in the fidelity of protein synthesis, it only includes the codon-anticodon interaction without considering the amino acid side chain. It is not known whether the ribosome has a specific interaction with the amino acid side chain or if the correctly charged tRNA behaves in such a way that brings this fidelity to protein synthesis process. To answer this question, we performed some preliminary calculations using numerical analysis on the misacylated tRNAs and compared the results with that of the cognate aminoacyltRNAs. Due to the large size of the molecule, we used 2-layered ONIOM (QM/MM) calculations. Interestingly, it was observed that only the initiator tRNAi met has a specific interaction with the amino acid side chain. (Keywords: Protein synthesis, aminoacyl-tRNA, ribosome.)